Охрана и воспроизводство бантенга (Bibos javanicus D'Alton) - Лобанов, Н.В.; Треус, В.Д. (Вестник зоологии, 1975)
Modern state of banteng in nature is dealt with. In 1960-1964 2 and I were delivered to Askaniya-Nova. In 1961-1974 25 calves were born, 14 of them in February March. The pregnancy lasts for 297±5 days. Two females gave the first offspring being 2 and half years old and two other above 3 years. The hybrids of banteng with Bos taurus indicus, Bos taurus macroceros, grey-ukrainian, red-german and red-steppe cattle (males sterile) were obtained.